Green Synthesis of Ni-Fe co-doped TiO2 (Ni0.05Fe0.05Ti0.9O2) Nanoparticles for Enhanced Supercapacitor Applications - Krishnakanth, E.; Kumar, P. Mohan (Asian Journal of Chemistry, 2026)
This work reports the green synthesis of Ni and Fe co-doped TiO2 nanocomposites via solution combustion using aloe vera gel as bio-fuel. The prepared Ni0.05Fe0.05Ti0.9O2 composition was confirmed by XRD and Raman spectroscopy, which showed anatase phase retention and successful substitution of Ti4+ by Ni2+ and Fe3+, inducing lattice distortion and local symmetry defects. SEM revealed reduced particle size and improved dispersion due to co-doping. Electrochemical studies including cyclic voltammetry, galvanostatic charge–discharge and impedance spectroscopy demonstrated enhanced capacitance, energy density and charge transfer dynamics in NiFeTiO2 compared to pure and Fe-doped TiO2. The NiFeTiO2 electrode achieved a high specific capacitance (140 F g–1), energy density (280 Wh/kg) and power density (54 kW/kg), highlighting the complementary role of binary doping in improving conductivity and pseudocapacitive behaviour. Overall, green synthesis and transition metal co-doping offer a sustainable route to high-performance supercapacitor electrode materials.